2018
DOI: 10.6007/ijarbss/v8-i5/4487
|View full text |Cite
|
Sign up to set email alerts
|

The Method of Managing Employee Motivation Based On a Halal Lifestyle

Abstract: In general, there are various methods of managing motivation that have been adopted by Islamic institutions. Nevertheless, a question remains whether there is any method that can enhance employees' motivation? What is the role of Islamic law and how can its principles be incorporated in the motivation management method? This needs to be emphasised as some motivation management methods, such as having a reward ceremony, are against Islamic law due to the serving of alcohol and the unethical interaction between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…In Malaysia, both public and private sector organizations found compensation as a strong and positive influential variable for motivation and work accomplishment as the sample was taken from 619 employees of both sectors (Ogbari et al , 2018). It is also recommended by researchers to align rewards management and objectives of employees such as motivation and task accomplishment to satisfy the employees (Samsudin and Ahmad, 2018). The study examined various variables including salary, promotion, benefits and appreciation to motivate employees involving employees of commercial banks of Pakistan (Karam, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In Malaysia, both public and private sector organizations found compensation as a strong and positive influential variable for motivation and work accomplishment as the sample was taken from 619 employees of both sectors (Ogbari et al , 2018). It is also recommended by researchers to align rewards management and objectives of employees such as motivation and task accomplishment to satisfy the employees (Samsudin and Ahmad, 2018). The study examined various variables including salary, promotion, benefits and appreciation to motivate employees involving employees of commercial banks of Pakistan (Karam, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Researchers also urge that incentive management and employee objectives be aligned for the purpose of employee satisfaction ( Samsudin and Ahmad, 2018 ). The current research studies the multiple variables that consist of promotion, benefits, salary, and appreciation toward encouraging employees of the Pakistani Commercial Banks ( Karam, 2017 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…It leads individual performance to a more effective performance management system. Managers will be very concerned about doing a good job because it impacts the allocation of rewards to motivate those who work for them (Samsudin & Ahmad, 2018). Therefore, achievement or performance will determine the reward of a worker to be motivated to ensure that performance will go well .…”
mentioning
confidence: 99%
“…Čečević, 2014;Bhatti et al, 2016;Khair et al, 2017;Van Herpen et al, 2005;Antoni et al, 2017;Van Eerde, 2015). It is shown that employees will be more easily motivated by rewards, especially financial rewards (Samsudin & Ahmad, 2018). Thereby, various human resource applications are used to develop motivation to improve workers' performance (Güngör, 2011).…”
mentioning
confidence: 99%
See 1 more Smart Citation